PDCD10 Gene Mutations in Multiple Cerebral Cavernous Malformations - Cigoli, Maria Sole (Public Library of Science, 2014)
Cerebral cavernous malformations (CCMs) are vascular abnormalities that may cause seizures, intracerebral haemorrhages, and focal neurological deficits. Familial form shows an autosomal dominant pattern of inheritance with incomplete penetrance and variable clinical expression. Three genes have been identified causing familial CCM: KRIT1/CCM1, MGC4607/CCM2, and PDCD10/CCM3. Aim of this study is to report additional PDCD10/CCM3 families poorly described so far which account for 10-15% of hereditary cerebral cavernous malformations. Our group investigated 87 consecutive Italian affected individuals (i.e. positive Magnetic Resonance Imaging) with multiple/familial CCM through direct sequencing and Multiplex Ligation-Dependent Probe Amplification (MLPA) analysis. We identified mutations in over 97.7% of cases, and PDCD10/CCM3 accounts for 13.1%. PDCD10/CCM3 molecular screening revealed four already known mutations and four novel ones. The mutated patients show an earlier onset of clinical manifestations as compared to CCM1/CCM2 mutated patients. The study of further families carrying mutations in PDCD10/CCM3 may help define a possible correlation between genotype and phenotype; an accurate clinical follow up of the subjects would help define more precisely whether mutations in PDCD10/CCM3 lead to a characteristic phenotype.